The Social Meaning Behind Recitation Hirzi Wa Hirsi at Miftahul Mubtadiin Islamic Boarding School Tanjunganom Nganjuk Indonesia - Yusriansyah, Mohammad Fadlil; Ubaidillah, Ubaidillah (IAIN Ponorogo, 2023)
Reciting Ayat Hirzi wa Hirsi regularly positively impacts both physical and psychological well-being. It shows that the Qur’an is more than just a book to lbe read. The Qur’an is also a tool for treatment in society, whether medical, non-medical, or psychological. By using data collection techniques such as observation, interviews, and documentation along with Karl Mannheim's sociology of knowledge about objective, expressive, and documentary, this article seeks to understand how students reacted to Mifathul Mubtadiin Islamic Boarding school’s recitation of the Ayat Hirzi wa Hirsi. The students are thus instructed secretly by mbah yai to recite Ayat Hirzi wa Hirsi at each dawn prayer. In terms of its objective meaning, it is a way of being aware of one's status as a santri or student. While expressively, it is understood as a medium for treatment, spiritual, psychological, and physiological therapy. Meanwhile, in the documentary, students are motivated to receive blessings.